Taking Stock of the Day that Disturbed the International Order - Molmisa, Ronald C. (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Review of Ken Booth and Tim Dunne's WORLDS IN COLLISION: Terror and the Future of Global Order.
Keywords: Ken Booth; Tim Dunne; Terrorism; global order